Pretreatment of Nicorandil Protects the Heart from Exhaustive Exercise-Induced Myocardial Injury in Rats. (6th January 2022) - Lv, Lei; Li, Lin; Zhu, Yiyong; Azhar, Anwar; Li, Yao; Wang, Yongyuan; Jin, Tao; Yin, Xin; Chen, Xi; Liu, Yu; Zhong, Yong
Abstract : Objective . Nicorandil has been widely used for the treatment of angina pectoris and myocardial infarction. The purpose of this study was to investigate whether nicorandil plays a protective role in exhaustive exercise (EE)-induced myocardial injury. Methods . Here, we applied the rat EE model and treated them with exercise preconditioning (EP, reported to protect the heart) or different doses of nicorandil gavage, respectively, to explore whether there are protective effects of single EP or nicorandil or a combination of both and the potential mechanism. Forty-nine male Sprague Dawley rats were randomly divided into control, EE, EP + EE, nicorandil (with low, middle, and high dose) + EE, and EP + nicorandil (middle dose) + EE. Blood samples and myocardial tissues were collected to analyze the myocardial injury-related index. Results . EE induced myocardial structural damage and altered the myocardial injury markers, which were partially reversed by pretreatment of nicorandil. In addition, oxidative stress and inflammation lead to the accumulation of reactive oxygen species (ROS) products and further damage to the myocardium, while pretreatment of nicorandil reduces the oxidative stress response and inflammation. Moreover, nicorandil suppressed the myocardial apoptosis induced by EE, as indicated by a decrease of Bax and caspase-3 expression and an increase of Bcl-2 expression. Finally, the pathway in which nicorandil plays a role may be involved in the endothelial nitric oxide synthase (eNOS)/nitric oxide (NO) pathway. Pretreatment of nicorandil increased the protein level of myocardial eNOS and NO production. Conclusion . Our result demonstrated that nicorandil has protective effects in EE-induced myocardial injury with dose-dependent effects. A combination of nicorandil and EP can further improve the protective effects. Taken together, nicorandil can be potentially used as an intervention method in EE-induced myocardial injury.